Discovery of a possible splashback feature in the intracluster light of MACS J1149.5+2223. Issue 1 (3rd August 2021) - Gonzalez, Anthony H; George, Tyler; Connor, Thomas; Deason, Alis; Donahue, Megan; Montes, Mireia; Zabludoff, Ann I; Zaritsky, Dennis
ABSTRACT: We present an analysis of the intracluster light (ICL) in the Frontier Field Cluster MACS J1149.5+2223 ( z = 0.544), which combines new and archival Hubble WFC3/IR imaging to provide continuous radial coverage out to 2.8 Mpc from the brightest cluster galaxy (BCG). Employing careful treatment of potential systematic biases and using data at the largest radii to determine the background sky level, we reconstruct the surface brightness profile out to a radius of 2 Mpc. This radius is the largest to which the ICL has been measured for an individual cluster. Within this radius, we measure a total luminosity of 1.5 × 10 13 L⊙ for the BCG plus ICL. From the profile and its logarithmic slope, we identify the transition from the BCG to ICL at r ∼ 70 kpc. Remarkably, we also detect an apparent inflection in the profile centred in the 1.2–1.7 Mpc (0.37–0.52 r 200 m ) radial bin, a signature of an infall caustic in the stellar distribution. Based upon the shape and strength of the feature, we interpret it as potentially being at the splashback radius, although the radius is smaller than theoretical predictions. If this is the splashback radius, then it is the first such detection in the ICL and the first detection of the splashback radius for an individual cluster. Similar analyses should be possible with the other Frontier Field clusters, and eventually with clusters observed by the Euclid and Roman missions.